Genetic Similarity Using MLST Amongst Campylobacter jejuni Isolates from Children with Diarrhea Symptoms and Broilers - Bhunikar Wongbundit (2018)
© 2016, The National Academy of Sciences, India. The aim of the present study was to investigate the genetic similarity amongst Campylobacter jejuni isolates from children with diarrhea symptoms and broilers in Chiang Mai, Thailand during 2002–2007. Sequence types of 12 isolates from children with symptoms of diarrhea and 9 isolates from broilers and other 42 Thai sequence types were determined by multilocus sequence typing. Cluster analysis was performed to determine the molecular relatedness of the isolates. Results showed diverse sequence types of C. jejuni isolated from both broilers and children. One isolate each from a broiler and a child shared a single sequence type (574). The majority of 13/16 sequence types belonged to previously reported sequence types in Thailand and two previously reported human sequence types were identified in broilers. The authors conclude that there is evidence of a genetic relationship between C. jejuni isolated from humans and broilers. MLST analysis of C. jejuni suggested that broilers are one of the sources of human infection in Chiang Mai, Thailand.